2009
DOI: 10.1051/0004-6361/200912995
|View full text |Cite
|
Sign up to set email alerts
|

The Chandra X-ray view of the power sources in Cepheus A

Abstract: The central part of the massive star-forming region Cepheus A contains several radio sources which indicates multiple outflow phenomena, yet the driving sources of the individual outflows have not been identified. We present a high-resolution Chandra observation of this region that shows the presence of bright X-ray sources with luminosities of L X 10 30 erg s −1 , consistent with active pre-main sequence stars, while the strong absorption hampers the detection of less luminous objects. A new source has been d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…At the distance of NGC 6334 I(N), the 6 cm flux densities of these objects would be 0.04-0.9 mJy, a range that includes both VLA2 and H 2 O-C4. It is interesting to note that HW 8 and HW 9 are both X-ray sources with HW 8 postulated to be a pre-main sequence star (due to its high median photon energy), while the softer, brighter, and more variable HW 9 is consistent with activity on a B-type star (Schneider et al 2009). In NGC 6334 I(N), a recent Chandra X-ray survey finds seven sources in the field of Figure 2, but none of the detections correspond in position to within 1.…”
Section: Vla 2 and H 2 O-c4mentioning
confidence: 93%
“…At the distance of NGC 6334 I(N), the 6 cm flux densities of these objects would be 0.04-0.9 mJy, a range that includes both VLA2 and H 2 O-C4. It is interesting to note that HW 8 and HW 9 are both X-ray sources with HW 8 postulated to be a pre-main sequence star (due to its high median photon energy), while the softer, brighter, and more variable HW 9 is consistent with activity on a B-type star (Schneider et al 2009). In NGC 6334 I(N), a recent Chandra X-ray survey finds seven sources in the field of Figure 2, but none of the detections correspond in position to within 1.…”
Section: Vla 2 and H 2 O-c4mentioning
confidence: 93%
“…X-rays have been observed from jets of some low-mass protostars (e.g., from DG Tau by Güdel et al (2008) and Schneider & Schmitt (2008)). X-ray emission has also been seen from some high-mass protostellar sources (e.g., from Cep A by Schneider et al (2009)). However, in general, the study of protostellar jets via X-rays is more limited compared to radio observations.…”
Section: Discussionmentioning
confidence: 98%
“…First, we set a conservative median energy cut M E > 4.5 keV that corresponds to a hydrogen column density N H ≈ 2 × 10 23 (assuming solar abundances in the intervening gas) or A v > 100 mag (assuming standard interstellar gas-to-dust ratio in the intervening material) using the calibration og Getman et al (2010). The threshold M E > 4.5 keV was chosen partly from past studies of star forming regions where previously known Class I protostars were found to have M E ≥ 4 keV (e.g., Getman et al 2007;Schneider et al 2009;Principe et al 2014), and partly from examination of the spatial distribution of sources in MYStIX fields under more and less strict criterion. Lower criterion like M E > 3.5 or M E > 4.0 increases the number of X-ray sources in the fields that are randomly located in the field rather than concentrated around dense molecular cloud cores ( §2.4) and increases the number of sources seen in the older field NGC 2362 where no Class 0/I protostars are expected.…”
Section: Selection Criteriamentioning
confidence: 99%